A method for estimation of accuracy of dose delivery with dynamic slit windows in medical linear accelerators - Ravichandran R; Binukumar J; Sivakumar S; Krishnamurthy K; Davis C (Journal of Medical Physics, 2008)
Intensity-modulated radiotherapy (IMRT) clinical dose delivery is based on computer-controlled multileaf movements at different velocities. To test the accuracy of modulation of the beam periodically, quality assurance (QA) methods are necessary. Using a cylindrical phantom, dose delivery was checked at a constant geometry for sweeping fields. Repeated measurements with an in-house designed methodology over a period of 1 year indicate that the method is very sensitive to check the proper functioning of such dose delivery in medical linacs. A cylindrical perspex phantom with facility to accurately position a 0.6-cc (FC 65) ion chamber at constant depth at isocenter, (SA 24 constancy check tool phantom for MU check, Scanditronix Wellhofer) was used. Dosimeter readings were integrated for 4-mm, 10-mm, 20-mm sweeping fields and for 3 angular positions of the gantry periodically. Consistency of standard sweeping field output (10-mm slit width) and the ratios of outputs against other slit widths over a long period were reported. A 10-mm sweeping field output was found reproducible within an accuracy of 0.03% (n = 25) over 1 year. Four-millimeter, 20-mm outputs expressed as ratio with respect to 10-mm sweep output remained within a mean deviation of 0.2% and 0.03% respectively. Outputs at 3 gantry angles remained within 0.5%, showing that the effect of dynamic movements of multileaf collimator (MLC) on the output is minimal for angular positions of gantry. This method of QA is very simple and is recommended in addition to individual patient QA measurements, which reflect the accuracy of dose planning system. In addition to standard output and energy checks of linacs, the above measurements can be complemented so as to check proper functioning of multileaf collimator for dynamic field dose delivery.